Introducing social theory - Jones, Pip; Bradbury, Liz , 1957-; Le Boutillier, Shaun (Polity Press, 2011)
New edition of a coherent, well-organized and thematic introduction to all the major thinkers, issues and debates in classical and contemporary social theory. Traces the development of social theory from the classical ideas of Durkheim, Marx and Weber to the latest contemporary theoretical controversies